2015
DOI: 10.1111/apt.13301
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogues improve health‐related quality of life in polycystic liver disease: a pooled analysis of two randomised, placebo‐controlled trials

Abstract: Summary Background Polycystic liver disease is associated with impaired health‐related quality of life (HRQL). Somatostatin analogues reduce hepatomegaly in polycystic liver disease. Aim To determine whether somatostatin analogues improve HRQL and to identify factors associated with change in HRQL in polycystic liver disease. Methods We pooled data from two randomized, double‐blind, placebo‐controlled trials that evaluated HRQL using the Short‐Form 36 (SF‐36) in 96 polycystic liver disease patients treated 6‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…Benefit is mostly seen during the first year and in women with severe PLD who are younger than age 48 years of age, because this subset of patients experiences the fastest rates of increase in LV. 10 Currently, somatostatin analogues are not approved for long-term use to slow PLD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Benefit is mostly seen during the first year and in women with severe PLD who are younger than age 48 years of age, because this subset of patients experiences the fastest rates of increase in LV. 10 Currently, somatostatin analogues are not approved for long-term use to slow PLD progression.…”
Section: Discussionmentioning
confidence: 99%
“…As liver volume appears to impact QoL, clinicians should check liver disease severity periodically and consider liver volume reducing therapies in severe hepatomegaly as a strategy to improve patients’ wellbeing. Indeed, research shows that reduction of liver volume with somatostatin analogues improves QoL in severe polycystic liver disease [46]. However, currently data is lacking on the effect of other therapies on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Several small clinical trials have shown beneficial effects of octreotide and lanreotide in patients with severe polycystic liver disease, particularly in premenopausal women (58). The Long-Acting Somatostatin on Disease Progression in Nephropathy due to ADPKD (ALADIN) trial showed a favorable trend for octreotide slowing TKV increase and GFR decline compared with placebo (59).…”
Section: Somatostatin Analogsmentioning
confidence: 99%